2013
DOI: 10.4161/rna.25274
|View full text |Cite
|
Sign up to set email alerts
|

HuR is a post-transcriptional regulator of core metabolic enzymes in pancreatic cancer

Abstract: Cancer cell metabolism differs from normal cells, yet the regulatory mechanisms responsible for these differences are incompletely understood, particularly in response to acute changes in the tumor microenvironment. HuR, an RNA-binding protein, acts under acute stress to regulate core signaling pathways in cancer through post-transcriptional regulation of mRNA targets. We demonstrate that HuR regulates the metabolic phenotype in pancreatic cancer cells and is critical for survival under acute glucose deprivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 46 publications
3
50
0
Order By: Relevance
“…2C), a transcript that is known to be stabilized during iron deprivation (32). DFO treatment also led to an increase in the stability of Hk2 and Slc2a1, which encode proteins involved in glucose metabolism, and whose expression can be influenced post-transcriptionally during nutrient stress via RNA-binding factors (33)(34)(35). Importantly, the half-lives of OxPhos transcripts determined from our analyses were similar to those from a global analysis of transcript turnover (36).…”
Section: Resultssupporting
confidence: 61%
“…2C), a transcript that is known to be stabilized during iron deprivation (32). DFO treatment also led to an increase in the stability of Hk2 and Slc2a1, which encode proteins involved in glucose metabolism, and whose expression can be influenced post-transcriptionally during nutrient stress via RNA-binding factors (33)(34)(35). Importantly, the half-lives of OxPhos transcripts determined from our analyses were similar to those from a global analysis of transcript turnover (36).…”
Section: Resultssupporting
confidence: 61%
“…Disparity in HuR expression and localization is likely to be heavily influenced by the tumor microenvironment, which can show significant interand intratumoral heterogeneity in terms of blood flow, oxygenation, and nutrient supply (47). We have shown that HuR is engaged under conditions of hypoglycemia and hypoxia (33). As such, HuR expression and cytoplasmic localization are expected to be high in regions within ovarian tumors with the least amount of vascularization (i.e., greatest hypoxia and hypoglycemia).…”
Section: Discussionmentioning
confidence: 88%
“…Our previous studies in preclinical pancreatic cancer models (33)(34)(35)(36)(37)(38), as well as studies by others (17,19,20,24,(39)(40)(41), provided the rationale for investigating HuR inhibition in ovarian tumors We first established that suppression of HuR expression reduces proliferation, anchorage-independent growth, and invasion of ovarian cancer cells in vitro. We further demonstrate HuR inhibitionmediated reduction in tumor growth rate, delay in ascites development, and extension of lifespan by nearly 1.5-fold in two different ovarian cancer mouse models, a xenograft model and an orthotopic model in which mice bear tumors throughout the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the cytoplasmic translocation of HuR has been reported in response to other stress conditions, including DNA damage and glucose deprivation. 49,50 Given our findings, modulating HuR levels or activity may constitute a rational pharmacological approach to manipulate VEGFA in disorders where it is desirable to inhibit neovascularization, such as diabetic retinopathy and cancer.…”
Section: Discussionmentioning
confidence: 84%